ANALISIS PENJADWALAN PROYEK PADA PEKERJAAN REPETITIF DENGAN METODE LINE OF BALANCE (LOB) DAN PRECEDENCE DIAGRAM METHOD (PDM) - Fepy Supriani (UNIB Press, 2022)
In housing projects, many work items are repetitive work. A project schedule that does not take into account repetitive work can lead to delays in project completion time. Proper scheduling methods will need to be applied so that project resources can be used effectively and efficiently. The research aims to analyze project scheduling and know the effectiveness of repetitive job scheduling projects in the building housing project. The study is perfomed by using Line Of Balance (LOB) which is a method of using the operating balance for each on-going performance work. Precedence Diagrams Method (PDM) shows critical tasks that can not be shown by LOB. The subject of this research is the construction of 10 houses sized 35/135 m2 in which 15 workers were employed. The results show that the duration needed to complete the project is 69 days. Compared to the existing duration (78 days) there is a 9 days difference. The effectiveness of scheduling is 11,5%. Keyword: Line of Balance, Precedence Diagram Method, Repetitive Project, Scheduling.